Capturing the Gender Gap in the Scope of Parenting Related Leave Policies Across Nations - Koslowski, Alison (Social Inclusion, 2022)
This article contributes to the conceptual and technical development of cross-national measurement and analysis of the gender gap in the scope of parenting related leave entitlements. That there is a gender gap in the scope of leave benefits is widely acknowledged, but it is rarely quantified. The nomenclature in use around leave policies is diverse and so a first step is to standardise categories and develop a unit of parenting related leave. There is considerable cross-national variation in the configuration of the scope of leave policies. As such, a second step is to consider how best to include the different dimensions of this scope (e.g., duration, payment level, individual parent versus family design) in an estimate of the gender gap in entitlement. Using data collated by the International Network on Leave Policies and Research, a gender gap indicator is created to contribute to our understanding of the inclusiveness of parenting related leave for men as compared to women. This indicator highlights that only two (Iceland and Norway) of 45 countries included in this analysis had achieved a zero-gender gap in terms of entitlement to ‘well-paid,’ individual parenting related leave during the first 18 months of a child’s life. The average gender gap for the countries in the analysis is between two to three months. Only seven countries offered more than two months leave to fathers as an individual entitlement. This is likely to be part of the explanation in many countries for lower leave taking practice by men compared to women.